2020
DOI: 10.3389/fgene.2019.01394
|View full text |Cite
|
Sign up to set email alerts
|

Systematically Dissecting the Function of RNA-Binding Proteins During Glioma Progression

Abstract: RNA-binding proteins (RBPs) play important roles in regulating gene expression and dysregulation of RBPs have been observed in various types of cancer. However, the role of RBPs during glioma progression, and particular in Chinese patients, is only starting to be unveiled. Here, we systematically analyzed the somatic mutation, gene expression patterns of 2949 RBPs during glioma progression. Our comprehensive study reveals several of highly mutated genes (such as ATRX, TTN and SETD2) and differentially expresse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In AML, the effects of RBM39 deletion on splicing further lead to preferential lethality for AML with spliceosome mutations, which provides a strategy for the treatment of those carrying RBP-splicing mutations (Wang E. et al, 2019 ; Villanueva et al, 2020 ). In glioma, although some studies report several RBPs related to a poor prognosis of these patients (Boucas et al, 2015 ; Bhargava et al, 2017 ; Barbagallo et al, 2018 ; Velasco et al, 2019 ; Wang J. et al, 2019 ; Lan et al, 2020 ; Wang et al, 2020 ), their potential clinical application, including for an individual prognostic risk assessment, lacks systematic evaluation. In the research on RBPs, some new technologies have been developed to enrich and extract RBPs and their homologous RNAs, such as the orthogonal organic phase separation (OOPS) (Villanueva et al, 2020 ), which is a fast, efficient, and reproducible method to purify cross-linked RNA-protein complexes in an unbiased manner, thus making it more efficient for identifying and studying new RBPs.…”
Section: Discussionmentioning
confidence: 99%
“…In AML, the effects of RBM39 deletion on splicing further lead to preferential lethality for AML with spliceosome mutations, which provides a strategy for the treatment of those carrying RBP-splicing mutations (Wang E. et al, 2019 ; Villanueva et al, 2020 ). In glioma, although some studies report several RBPs related to a poor prognosis of these patients (Boucas et al, 2015 ; Bhargava et al, 2017 ; Barbagallo et al, 2018 ; Velasco et al, 2019 ; Wang J. et al, 2019 ; Lan et al, 2020 ; Wang et al, 2020 ), their potential clinical application, including for an individual prognostic risk assessment, lacks systematic evaluation. In the research on RBPs, some new technologies have been developed to enrich and extract RBPs and their homologous RNAs, such as the orthogonal organic phase separation (OOPS) (Villanueva et al, 2020 ), which is a fast, efficient, and reproducible method to purify cross-linked RNA-protein complexes in an unbiased manner, thus making it more efficient for identifying and studying new RBPs.…”
Section: Discussionmentioning
confidence: 99%
“…They found IGF2BP3-positive high-grade gliomas showed shorter OS and confirmed the role of IGF2BP3 as a marker of poor outcomes ( Del Gobbo et al, 2015 ). Wang analyzed the transcriptome alterations of RBPs and found that the expression levels of SNRPN and IGF2BP3 were significantly associated with the OS of patients in all grades ( Wang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research demonstrates that several RBPs have closely correlations with the malignant behaviors of glioma ( 14 ). Nevertheless, the functions of most of the RBPs in glioma tumorigenesis remain unclear ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, their roles still require to be explored in depth via further functional studies. Recent studies suggest that several RBPs exhibit significant associations with clinical outcomes of glioma patients, such as SNRPN and IGF2BP3 ( 14 ). Hence, targeting RBPs appears to be promising strategies for the development of novel treatment against cancers.…”
Section: Introductionmentioning
confidence: 99%